DELIK POLITIK DALAM HUKUM PIDANA INDONESIA - Hardiago, David (UI Scholars Hub, 2020)
According to Indonesian penal law, an act is considered to be a criminal act based on the principle of legality. Problem arise when political crime is associated with the principle of legality, that said problem is related to the definition of political crime that is not stipulated in any of statutory provisions and/or regulations in Indonesia. This legal research aims to answer two legal problems raised by the Author, those are: Firstly, to determine the parameter of political crime in Indonesia. Secondly, to elaborate on the projection on how political crime should be stipulated in the future. The research in this study used normative legal research in order to find answers for legal problems elaborated by the Author. Secondary data collection is supported by some approaches, those are statutory approach, conceptual approach as well as comparative approach. Those aforementioned shall be constructed qualitatively in order to reach the conclusion using deductive and inductive method alternatively.